Flow patterns for muddy material in a rotating drum - Liu, Ko-Fei; Ai, Yi-An (Italian journal of engineering geology and environment, 2011)
We perform rheological measurements in a rotating drum. As a starting point for using formula to calibrate rheological measurements, we first identify the possible flow phenomenon in the drum. The experiments were conducted in a drum with 0.5 m inner radius and 0.2 m width. The material used is a Kaolin/ water mixture. The rotating speeds varied from 0 rpm to 40 rpm. The sample amount used in experiments must be large enough to assure that the flow length is much larger than its height. The three flow patterns discovered are Sliding, Swinging, and Circling. Among the three basic categories, there are other variations in each category. Some ofthe variations are unsteady patterns. We delineate the occurrence of the observed motion patterns in a diagram asa function of rotation speed and kaolin concentration.